PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTON PADA KARYAWAN - Krisna Nur Afrizal; Hikmah Ayu Kinanti; Ella Alicia Nur Affiffah; Dani Rizana (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the influence of job satisfaction and work stress on employee turnover intention. Turnover intention refers to the employee's intention to leave their job, which can be influenced by various factors, including job satisfaction and work stress. The research method used is a descriptive approach by collecting data from various literature sources. The results of the literature review indicate a significant relationship between job satisfaction and turnover intention, where high job satisfaction tends to reduce employees' intention to leave. Conversely, high work stress contributes to an increase in turnover intention. This study concludes that management needs to create a supportive work environment to enhance employee satisfaction and reduce stress levels in order to mitigate turnover intention.